THEORETICAL BASIS OF PROJECT TRAINING IN HIGH SCHOOL STUDENTS - S. A. Tsyplakova (Вестник Мининского университета, 2017)
The author substantiates project learning of students in higher education. As the author examines the theoretical foundations and methodological approaches (prognostic, system, student-activity), principles (parity, humanization, creative modeling, personal orientation, variability), the main provisions (predictability, consistency, focus on activities).